RNA sequencing-based exploration of the effects of far-red light on lncRNAs involved in the shade-avoidance response of D. officinale - Hansheng Li; Wei Ye; Yaqian Wang; Xiaohui Chen; Yan Fang; Gang Sun (PeerJ, 2021)
Dendrobium officinale (D. officinale) is a valuable medicinal plant with a low natural survival rate, and its shade-avoidance response to far-red light is as an important strategy used by the plant to improve its production efficiency. However, the lncRNAs that play roles in the shade-avoidance response of D. officinale have not yet been investigated. This study found that an appropriate proportion of far-red light can have several effects, including increasing the leaf area and accelerating stem elongation, in D. officinale. The effects of different far-red light treatments on D. officinale were analysed by RNA sequencing technology, and a total of 69 and 78 lncRNAs were differentially expressed in experimental group 1 (FR1) versus the control group (CK) (FR1-CK) and in experimental group 4 (FR4) versus the CK (FR4-CK), respectively. According to GO and KEGG analyses, most of the differentially expressed lncRNA targets are involved in the membrane, some metabolic pathways, hormone signal transduction, and O-methyltransferase activity, among other functions. Physiological and biochemical analyses showed that far-red light promoted the accumulation of flavonoids, alkaloids, carotenoids and polysaccharides in D. officinale. The effect of far-red light on D. officinalemight be closely related to the cell membrane and Ca2+ transduction. Based on a Cytoscape analysis and previous research, this study also found that MSTRG.38867.1, MSTRG.69319.1, and MSTRG.66273.1, among other components, might participate in the far-red light signalling network through their targets and thus regulate the shade-avoidance response of D. officinale. These findings will provide new insights into the shade-avoidance response of D. officinale.